The Sufi phenomenology of love based on the thoughts of Rabia Al-Adawiyya and Edith Stein - Bunyadzade, Konul (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article contributes to research on the consideration of the phenomenon of Love through a comparison of the thoughts of Sufi thinker Rabia al-Adawiyya (713-801) and phenomenological philosopher Edith Stein (1891-1942). The author studies the poems of Rabia and the final work of Edith Stein, where she discussed her views on divine love, “Science of Cross”. The main aim of the article is a search for the crossing point between Sufism and Phenomenology. The author considers three stages of phenomenological reduction: faith, hope and love. First, the heart is considered as a noematic core and the result of epoché. The second part of the article is an investigation into the second stage of phenomenological reduction, hope, which is studied as a transition between rational and irrational thoughts. In the third part of the article, divine love is investigated as a process of perfection in Sufism and of phenomenological reduction in phenomenology. In conclusion, the essence of love is presented on the basis of Sufi phenomenology, where the principles of Sufism and phenomenology are in contact. In other words, the consideration of love is a method of representing Sufi phenomenology as a new philosophical doctrine.